2019
DOI: 10.1007/s00018-019-03380-2
|View full text |Cite
|
Sign up to set email alerts
|

The common message of constraint-based optimization approaches: overflow metabolism is caused by two growth-limiting constraints

Abstract: Living cells can express different metabolic pathways that support growth. The criteria that determine which pathways are selected in which environment remain unclear. One recurrent selection is overflow metabolism: the simultaneous usage of an ATP-efficient and-inefficient pathway, shown for example in Escherichia coli, Saccharomyces cerevisiae and cancer cells. Many models, based on different assumptions, can reproduce this observation. Therefore, they provide no conclusive evidence which mechanism is causin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 45 publications
1
57
0
Order By: Relevance
“…Concurrently, we introduced a revised mechanism for carbon storage, effectively treating glycogen as an independent component of biomass. This configuration makes it possible for glycogen to be accumulated and depleted at variable rates (Figure 1), aligning with the overflow metabolism hypothesis (Szul et al, 2019; de Groot et al, 2020). Other key modifications induced by the ReFill algorithm and subsequent manual curation (see Methods) include the completion of the Entner-Doudoroff (ED) pathway, recently discovered in cyanobacteria (Chen et al, 2016) and proposed as the primary Prochlorococcus glucose metabolism pathway under mixotrophic conditions (Biller et al, 2018).…”
Section: Resultssupporting
confidence: 79%
“…Concurrently, we introduced a revised mechanism for carbon storage, effectively treating glycogen as an independent component of biomass. This configuration makes it possible for glycogen to be accumulated and depleted at variable rates (Figure 1), aligning with the overflow metabolism hypothesis (Szul et al, 2019; de Groot et al, 2020). Other key modifications induced by the ReFill algorithm and subsequent manual curation (see Methods) include the completion of the Entner-Doudoroff (ED) pathway, recently discovered in cyanobacteria (Chen et al, 2016) and proposed as the primary Prochlorococcus glucose metabolism pathway under mixotrophic conditions (Biller et al, 2018).…”
Section: Resultssupporting
confidence: 79%
“…Concurrently, we introduced a revised mechanism for carbon storage, effectively treating glycogen as an independent component of biomass. This dynamic implementation of glycogen storage, introduced here in dFBA, makes it possible for glycogen to be accumulated and depleted at variable rates ( Figure 1 ), aligning with the overflow metabolism hypothesis ( Szul et al, 2019 ; de Groot et al, 2020 ). Other key modifications induced by the ReFill algorithm and subsequent manual curation (see section Materials and Methods) include the completion of the Entner–Doudoroff (ED) pathway, recently discovered in cyanobacteria ( Chen et al, 2016 ) and proposed as the primary Prochlorococcus glucose metabolism pathway under mixotrophic conditions ( Biller et al, 2018 ; Muñoz-Marín et al, 2020 ).…”
Section: Resultsmentioning
confidence: 58%
“…Nutrient-dependent regulation membrane permeability to antibiotics ( Figure 3E) can be a result of different metabolic pathways. It has been observed that E.coli cells have different metabolic pathways for nutrients depending on the growth conditions [53]. Furthermore, if the cells are subjected to a nutrient downshift, the proteome reallocates such that a larger fraction of proteins is allocated to the sector responsible for carbon catabolism which in turn reduces the available proteome fraction for other sectors [54,55].…”
Section: Mechanistic Origin Of Ribosomal Tradeoff Between Growth and mentioning
confidence: 99%